Tree-ring width series of white spruce (Picea glauca) trees (Coppermine River Canada) 1676 - 2003 ... - D’Arrigo, Rosanne; Buckley, Brendan; Oelkers, Rose; Levesque, Mathieu; Andreu-Hayles, Laia (NSF Arctic Data Center, 2023)
Tree-ring width records of white spruce (Picea glauca [Moench] Voss) trees sampled along the Coppermine River (67º23’N / 115º92’W, 210 m a.s.l.) in 2004. When using this dataset, please cite: Lévesque, M., Andreu-Hayles, L., D’Arrigo, R., Oelkers, R., & Buckley, B. M. (2023). Non-linear Growth and Physiological Responses of White Spruce at North American Arctic Treeline. Journal of Geophysical Research: Biogeosciences, 128, e2022JG007096. https://doi.org/10.1029/2022JG007096 Project abstract: Temperatures in Arctic and subarctic North America are rising and are projected to continue to rise. Furthermore, atmospheric carbon dioxide is increasing around the globe. This project evaluates the response of white spruce to these ongoing changes. It uses archived samples from ten sites, standard tree-ring methodologies supplemented by novel chemical analyses, and numerical models to understand tree growth response to changing environmental drivers. Extending traditional tree-ring width and maximum latewood ...